Examining Entrepreneurial intention of Generation Z in Indonesia - Bernadi, Benedikta Anindaya; Harnadi, Bernardinus; Prawihatmi, Chatarina Yekti (Soegijapranata Catholic University, 2025)
This study aims to examine the entrepreneurial intentions of generation Z in Indonesia. This study reveals the factors that influence the entrepreneurial intentions of generation Z and analyzing the relationship between these factors. The study was conducted using the FGD method on young entrepreneurs of generation Z to obtain input on the conditions of young entrepreneurship, especially generation Z. Reviewing the previous related literatures on entrepreneurial intention research were used to obtain a selection of factors that influence entrepreneurial intentions among young people. Models and hypotheses were built based on input from FGDs and previous related studies and then they were tested using the questionnaire data from survey techniques. Data testing was carried out using descriptive statistical methods, validity tests, reliability tests, and correlation tests using SPSS. Analysis of individual respondent factors was also carried out to reveal the characteristics of generation Z. The causality test using correlation technic were used to reveal the relationships between the factors studied. The output of this study is a model of entrepreneurial behaviors (entrepreneurial intentions) of generation Z in Indonesia. The results of this study reveal that factors naming Attitude towards money, Entrepreneurship education, Advance in technology, and Entrepreneurship efficacy have association with Entrepreneurship Intention. All factors also have a relationship with each other. Surprisingly, the personal factor Gender only has a relationship with Entrepreneurship education. Men and women have different relationships; women have a stronger relationship with entrepreneurship education. Meanwhile, Age has no relationship with all factors in this study. These results provide insight to entrepreneurship educators, the government, and stakeholders regarding the progress of young entrepreneurship in Indonesia. This insight is useful in assisting young people, especially generation Z, in entering and engaging in the entrepreneurship.